2015
DOI: 10.4103/0366-6999.152485
|View full text |Cite
|
Sign up to set email alerts
|

Plasma α1-antitrypsin

Abstract: Background:As an acute phase protein, α1-antitrypsin (AAT) has been extensively studied in acute coronary syndrome, but it is unclear whether a relationship exists between AAT and stable angina pectoris (SAP). The purpose of the present study was to investigate the association between AAT plasma levels and SAP.Methods:Overall, 103 SAP patients diagnosed by coronary angiography and clinical manifestations and 118 control subjects matched for age and gender were enrolled in this case-control study. Plasma levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, Brunetti et al ( 41 ) detected elevated AAT levels in the plasma of patients with unstable angina pectoris. In 2015, Zhao et al ( 21 ) first indicated that the plasma concentrations of AAT in patients with stable angina pectoris were significantly higher than those in a healthy control population and positively correlated with the severity of coronary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Brunetti et al ( 41 ) detected elevated AAT levels in the plasma of patients with unstable angina pectoris. In 2015, Zhao et al ( 21 ) first indicated that the plasma concentrations of AAT in patients with stable angina pectoris were significantly higher than those in a healthy control population and positively correlated with the severity of coronary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma AAT levels have been demonstrated to correlate with both the presence and severity of coronary stenosis in patients with stable angina pectoris (SA) ( 21 ). However, at present, available studies on the association between plasma AAT concentrations and the severity of ACS are sparse and insufficient ( 21 ). Thus, it remains elusive whether plasma AAT is correlated with ACS.…”
Section: Introductionmentioning
confidence: 99%